The making of "Jew Clubs": performing Jewishness and antisemitism in European football and fan cultures - Brunssen, Pavel (Studies in antisemitism, 2025)
"Take a deep dive into four European football clubs that are widely known as '"Jew Clubs."' Though none of these football clubs are explicitly Jewish, learn how they have become arenas for negotiating ideas about Jewishness and antisemitism in contemporary European society. In The Making of "Jew Clubs", author Pavel Brunssen uses FC Bayern Munich, Austria Vienna, Ajax Amsterdam, and Tottenham Hotspur as case studies to investigate how post-Holocaust, European societies engage with the Jewish community and how Jews navigate their identities within them. Using an array of primary sources, he argues that football is a contested space for shared memory cultures and collective identities. The Making of "Jew Clubs" is an indispensable read for anyone interested in European football, cultural studies, Jewish history, memory cultures, and the evolving dynamics of antisemitism in contemporary European societies"-- Provided by publisher